Effect of physical activity on changes in weight and aerobic capacity during an 18-month behavioral weight loss intervention - Seth A. Creasy; Danielle M. Ostendorf; Laura Kaizer; Rebecca Rosenberg; Matthew J. Breit; Daniel H. Bessesen; Edward L. Melanson; Victoria A. Catenacci (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background The objective of this secondary analysis was to examine the effect of MVPA and the time of day that MVPA (i.e., morning vs. evening) is performed on long-term changes in body weight and aerobic capacity. Methods Adults with overweight and obesity (n = 105) enrolled in an 18-month behavioral weight loss intervention involving a reduced calorie diet and a supervised exercise program. Participants were encouraged to increase their bouted MVPA (i.e., MVPA accumulated in bouts ≥ 10 min) to 300 min/wk. Body weight, body composition, aerobic capacity, and physical activity were assessed at 0, 6, 12, and 18 months. Participants were categorized based on whether they increased bouted MVPA by ≥ 150 min/wk during the supervised exercise program. Linear regression was used to examine the effect of increasing bouted MVPA on weight loss and aerobic capacity. Similar methods were used to examine the effect of time of day of MVPA on weight loss and aerobic capacity. Results Participants who increased bouted MVPA by ≥ 150 min/wk during the supervised exercise program had greater weight loss, fat loss, and increases in aerobic capacity at 18 months compared to participants who increased bouted MVPA by < 150 min/wk. Amongst participants who increased bouted MVPA by ≥ 150 min/wk, the time of day of MVPA had no significant effect on weight loss or aerobic capacity. Conclusions Increasing bouted MVPA by ≥ 150 min/wk improves weight loss and aerobic capacity during a behavioral weight loss intervention which includes caloric restriction. MVPA earlier and later in the day is beneficial for weight management and cardiorespiratory fitness. Trial registration Clinicaltrials.gov (NCT01985568) on October 24, 2013.